Evolutionary taxonomy of uncertainty - Stokłosa, Paweł (Ruch Prawniczy, Ekonomiczny i Socjologiczny, 2026)
Uncertainty has long occupied a central position in economic thought, shaping both theoretical debates and policy design. Existing taxonomies of uncertainty typically rely on fixed distinctions, such as ergodic and non-ergodic states of reality, and therefore remain largely static and teleological. As a result, they fail to capture the historically contingent, cumulative, and institutionally embedded character of uncertainty. Building on Thorstein Veblen’s critique of taxonomic science and his evolutionary framework, this article addresses this gap by developing an evolutionary taxonomy of uncertainty that integrates post-Keynesian insights on expectations with Veblen’s concepts of cumulative change and the ceremonial-industrial value dichotomy. The article integrates post-Keynesian expectations approaches with Veblen’s institutional insights, particularly his distinction between ceremonial (pecuniary) and industrial (instrumental) values. Methodologically, the study employs an integrative review of the literature and a conceptual comparative framework that reinterprets Davidson’s uncertainty taxonomy through an evolutionary lens. The proposed taxonomy identifies four regimes of evolutionary uncertainty – ceremonially stable, ceremonially unstable, industrially stable, and industrially unstable – defined by the interplay between institutional functions and the perceived stability of core expectations. The paper demonstrates that uncertainty evolves through institutional adaptation, narrative reconstruction, and shifts in agents’ confidence in fundamental assumptions about the economic environment. The main contribution lies in developing a non-teleological and institutionally grounded taxonomy of uncertainty that offers a more realistic analytical tool for institutional analysis, crisis research, and economic policy design.